Remarkable hydrogen storage properties of MgH2 doped with VNbO5. Issue 6 (22nd January 2018) - Valentoni, Antonio; Mulas, Gabriele; Enzo, Stefano; Garroni, Sebastiano
Abstract : The present work concerns the catalytic effect of VNbO5, a ternary oxide prepared via a solid-state route, on the sorption performance of MgH2 . Abstract : The present work concerns the catalytic effect of VNbO5, a ternary oxide prepared via a solid-state route, on the sorption performance of MgH2 . Three doped systems, namely 5, 10 and 15 wt% VNbO5 –MgH2 have been prepared by ball milling and thoroughly characterized. Hydrogen sorption, evaluated by temperature programmed desorption experiments, revealed a significant reduction of the desorption temperature from 330 °C for the un-doped sample (prepared and tested for comparison) to 235 °C for the VNbO5 -doped sample. Furthermore, more than 5 wt% of hydrogen can be absorbed in 5 minutes at 160 °C under 20 bar of hydrogen, which is remarkable compared to the 0.7 wt% achieved for the un-doped system. The sample doped with 15 wt% of additive, showed good reversibility: over 5 wt% of hydrogen with negligible degradation even after 70 consecutive cycles at 275 °C and 50 cycles at 300 °C. The kinetics analysis carried out by Kissinger's method exhibited a considerable reduction of the activation energy for the desorption process. Finally, pressure-composition-isotherm experiments conducted at three different temperatures allowed estimating the thermodynamic stability of the system and shed light on the additive role of VNbO5 .